PHYTOREMEDIATION OF ARSENIC BY Phragmites australis, Colocasia esculenta AND Canna indica USING A NOVEL SEMI-HYDROPONICS SYSTEM (Applied Biological Research, 2023)
Hydroponics system is a potential and cost-effective technique for waste water treatment. Aquatic macrophytes are more efficacious material for  phytoremediation due to their physiological and morphological properties.  We designeset of three hydroponics (PVC pipes) interconnected in series o as the inlet of first hydroponic was connected from tank containing  arsenic (As) contaminated wastewater and its outlet with the second as its  inlet and outlet of second with the third one. In each hydroponic, 6 pots (filled with soil and compost and referred as semi-hydroponics systems viz.,  SHS-1, SHS-2 and SHS-3) with pre-established single individual of  Phragmites australis, Colocasia esculenta and Canna indica were placed in SHS-1, SHS-2 and SHS-3, respectively. Wastewater was retained in each  SHS for 10 days (hydraulic retention time); and passed from 1st to 2nd and  then to 3rd one in series at every 10 days intervals. The growth performances  of selected macrophytes were compared with and control plants maintained  in freshwater hydroponics. Wastewater significantly enhanced shoot length,  proline content, chlorophyll content and sugar content of leaf tissue of all  the studied macrophytes. The plants and soil sediments absorbed As from  the waste water efficiently and retained amount of As in phytoremediated  spent wastewater from third semi-hydroponic system (SHS-3) was below  limit of quantification of ICP-MS. The semi-hydroponic system in this  experiment was found to be an efficient, cost-effective, easy to be installed  and globally applicable phytoremediating technique.
Keywords: Arsenic; Canna indica; Colocasia esculenta; Phragmites australis; phytoremediation; semi-hydroponics; wastewater